The Impact of Healthcare Service Quality on Patient Satisfaction at University Health Center - Yunus, Noor’ain Mohamad; Abdullah, Mohd Zulkifli; binti Ramdan, Nurul Fatihah; Alnuaimi, Huda Al Shaiba Bedaia Safsouf (Information Management and Business Review, 2024)
Patient satisfaction is a critical aspect of healthcare service quality that needs to be periodically evaluated and improved. Understanding various factors, including empathy, assurance, reliability, tangibility, and responsiveness, is necessary to enhance healthcare quality and improve patient satisfaction. This research aims to investigate the level of patient satisfaction and the relationship between patient satisfaction and service quality, using the five SERVQUAL model as a framework. A positivist approach was used to explore the relationship between variables. Data collection was carried out for two weeks using online questionnaires. For this research, 120 UiTM respondents were chosen using convenience sampling. Data was analyzed using SPSS version 29. The findings revealed a significant positive relationship between tangibility, responsiveness, and empathy with patient satisfaction. This study highlights the importance of regularly assessing patient satisfaction and identifying areas for improvement in healthcare service quality. University health centers can enhance patient satisfaction and provide better student healthcare services by focusing on tangibility, responsiveness, and empathy.